Freedom, Earth, World: An Arendtian Eco-politics of Dissent - Wren, Jonathan (HannahArendt.net, 2022)
This article draws upon Arendt offering a phenomenological defence of democratic freedom and the right to dissent. There are, broadly speaking, three parts to the paper. The first part investigates the distinction between the artificiality of the world and materiality of the earth (that cannot be entirely separated) which has important consequences for her discussion of alienation. Therefore, under an Arendtian diagnosis, as we seek to rebalance human life on the planet, we may also need to re-acquaint ourselves with the complex space that constitutes the common world. The second part concentrates on Arendt’s descriptions of the world which are underscored by a sense of distance which both relates and separates members. The third part connects this phenomenology of world to Arendt’s more explicitly political works. By looking at its relationship to her notion of freedom, I propose a reading of the concept which emphasises the role of dissent, as a key element of her understanding of political intersubjectivity. Within the context of environmentalist politics, this account can be used to critique the tendency to reduce politics to a techne; which may resist both romantic calls for an organic return to nature, or promises to technologically liberate humankind from the limitations prescribed by our planetary condition.